Eales’ Disease: When the Rare Sounds Frequent - Beatriz Oliveira Lopes; Margarida Sena Brízido; Ana Isabel Reis; Margarida Maria Miranda; Susana Morais Pina (Case Reports in Ophthalmological Medicine)
Eales’ disease is a peripheral occlusive retinal phlebitis, with an unclear pathogenesis. The classic association with hypersensitivity to Mycobacterium tuberculosis protein infers that immunologic disturbance may be involved. Here, we described three cases of Eales’ disease. All patients are Caucasian men aged 27-58 years and presented with vitreous hemorrhage and/or peripheral venous vasculitis. Tuberculin skin sensitive test (Mantoux screening test) and interferon-gamma release assay (IGRA) were positive in all patients. Therapeutic approach included antituberculosis therapy and systemic steroids, associated or not to immunosuppressive therapy, and retinal scatter photocoagulation in all cases. Antivascular endothelial grow factor (VEGF) intravitreal injections were also required in two cases. Since various retinal diseases can resemble this presentation, Eales’ disease is considered a diagnosis of exclusion. Early diagnosis and appropriate therapeutic approach are both essential to accomplish disease control and reduce ophthalmologic complications.